Comparability of three mobile respiratory gas analyzers - Brandes, M.; Klein, H.; Ginsel, S.; Heitmann, A. (Sportwissenschaft, 2015)
The aim of the study was to evaluate the comparability of three common mobile respiratory gas analyzers during exercise, to analyze whether findings from studies using one of the three devices tested in our study could be used interchangeably. As a simultaneous measurement with all three devices was technically not feasible, we chose a protocol with increasing workload but within submaximal exercise conditions, and changed the devices in a random order within each condition. Therefore, we chose trained amateur endurance athletes to meet the long exercise duration required by the study protocol. However, this does not alter the generalizability, for example, for measurements of CRF under a health perspective. In general, the means for VO2 and VE were well to highly comparable between the three devices tested according to the corrected correlation coefficients from 0.89 to 0.99 and high ICC between devices ranging from 0.92 to 0.95. However, the CIs demonstrate that at least acceptable consistency is given between the devices taking the variation between all devices into account. Noteworthy, the coefficient of variance was significantly pronounced in the OM system compared with MM and K4b2, especially in the estimation of VE. Similar to the inter-device reliability, the results prove at least sufficient intradevice reliability for all devices. This findings are in line with previous studies for the OM (Rosdahl et al., 2010), the K4b2 (Darter, Rodriguez, & Wilken, 2013; Duffield, Dawson, Pinnington, & Wong, 2004) and the MM (Macfarlane & Wong 2012; Meyer, Georg, Becker, & Kindermann, 2001). Conclusion: Using one of the three devices included in our study allows for an at least acceptable comparability of the results for VE and VO2.